CAR-iNKT cells targeting clonal TCRVβ chains as a precise strategy to treat T cell lymphoma - Rowan, Aileen G.; Ponnusamy, Kanagaraju; Ren, Hongwei; Taylor, Graham P.; Cook, Lucy B. M.; Karadimitris, Anastasios (Frontiers in Immunology, 2023)
Introduction Most T cell receptor (TCR)Vβ chain-expressing T cell lymphomas (TCL) including those caused by Human T cell leukaemia virus type-1 (HTLV-1) have poor prognosis. We hypothesised that chimeric antigen receptor (CAR)-mediated targeting of the clonal, lymphoma-associated TCRβ chains would comprise an effective cell therapy for TCL that would minimally impact the physiological TCR repertoire. Methods As proof of concept, we generated CAR constructs to target four TCRVβ subunits. Efficacy of the CAR constructs was tested using conventional T cells as effectors (CAR-T). Since invariant NKT (iNKT) cell do not incite acute graft-versus-host disease and are suitable for ‘off-the-shelf’ immunotherapy, we generated anti-TCRVβ CAR-iNKT cells. Results We show that anti-TCRVβ CAR-T cells selectively kill their cognate tumour targets while leaving >90% of the physiological TCR repertoire intact. CAR-iNKT cells inhibited the growth of TCL in vivo, and were also selectively active against malignant cells from Adult T cell leukaemia/lymphoma patients without activating expression of HTLV-1. Discussion Thus we provide proof-of-concept for effective and selective anti-TCRVβ CAR-T and -iNKT cell-based therapy of TCL with the latter providing the option for ‘off-the-shelf’ immunotherapy.